Awareness of parents of preschool children about selected heavy metals in food - Magdalena Dolibóg; Weronika Osmala-Kurpiewska (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Introduction: Human activity has contributed to the widespread distribution of heavy metals in the natural environment. The effects of exposure to heavy metals may not become apparent until many years later. Understanding and understanding the health risks of heavy metals in food is essential to protect children's health. The study aimed to assess the level of knowledge about heavy metals, their occurrence in food, and the health risks to children from eating food contaminated with heavy metals. Material and methods: The research tool was the author's questionnaire, consisting of the "specification" part and closed questions, mainly of a single choice. The study group consisted of 100 parents of two kindergartens located in the Silesian voivodeship. The results of the survey questionnaire were developed in Microsoft Office Excel 2019. Statistica 13 (StatSoft) was used for statistical analysis (chi-square test) and statistical significance was assumed at the level of α = 0.05. Results: Parents of preschool-age children are not aware of the associated risks of exposure to heavy metals. Most of the respondents did not read the general information on the presence of heavy metals in food products. Conclusions: The awareness of preschool-age parents about selected heavy metals in food is low. It is recommended to implement educational activities to increase the level of parental knowledge about possible health consequences and ways to reduce the health risk resulting from exposure to heavy metals through food.